2001
DOI: 10.1088/0022-3727/34/17/319
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport and ac electrical properties of carbon black polymer composites

Abstract: The dielectric behaviour of various carbon black polymer composites has been characterized by the critical frequency ωc denoting the crossover from the dc plateau of the conductivity to its frequency dependent ac behaviour. The critical frequency can be related to the dc conductivity using a power law, ωc∝σdcz, with the exponent z. Presently accepted models predict z to be greater than one when varying the filler content. However, in accordance with published experimental results this work shows that z is rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 16 publications
3
62
0
4
Order By: Relevance
“…9 Some authors have shown that the increase of the CB agglomerates can be related to the increase of the critical CB weight content and makes narrow percolation range. [7][8][9] A certain effect of morphology on the electrical behavior of composites was shown for the composites of polymer blends and CB. [7][8][9] Patnaik et al have studied electrical conductivity of HDPE-CB composites using Positron Annihilation Lifetime Spectroscopy and suggested existence of three different morphological domains with different free volumes.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…9 Some authors have shown that the increase of the CB agglomerates can be related to the increase of the critical CB weight content and makes narrow percolation range. [7][8][9] A certain effect of morphology on the electrical behavior of composites was shown for the composites of polymer blends and CB. [7][8][9] Patnaik et al have studied electrical conductivity of HDPE-CB composites using Positron Annihilation Lifetime Spectroscopy and suggested existence of three different morphological domains with different free volumes.…”
Section: Resultsmentioning
confidence: 92%
“…[7][8][9] A certain effect of morphology on the electrical behavior of composites was shown for the composites of polymer blends and CB. [7][8][9] Patnaik et al have studied electrical conductivity of HDPE-CB composites using Positron Annihilation Lifetime Spectroscopy and suggested existence of three different morphological domains with different free volumes. 14 In our experiments, LDPE as a crystalline branched polymer has a morphology with the possibility of formation of structural parts in percolation range.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Based on previous transmission electron micrograph results [19,42], the incorporated CB volume fraction (ca. 30 -40 vol%), and allowable tunneling distances [42,43], we anticipate the average particle spacing to be on the order of the particle diameter. In other words, the LbL film could be represented as a series of electrodes separated by 10 -30 nm gaps that are filled with electrolyte solution and a polyelectrolyte matrix.…”
Section: Possible Lbl Contribution To Total Impedancementioning
confidence: 99%
“…For a particle density of CBNPs, η was calculated using 1.80 g cm −3 obtained from the literature (Jäger et al, 2001). Sticking efficiency can be determined from the following equation (Tufenkji and Elimelech, 2004):…”
Section: Colloid Filtration Theorymentioning
confidence: 99%